The Existence of Management Rights (HPL) in Property Investment: Legal Certainty and Economic Opportunities - Soegianto, Soegianto (Jurnal Hukum Khaira Ummah, 2026)
Management Rights (HPL) are state-issued control rights, the implementation of which is partially delegated to rights holders, such as government agencies, local governments, or certain public legal entities. In Indonesia's property investment ecosystem, HPL plays a strategic role as a legal instrument that enables the private sector to utilize state assets. This legal relationship pattern is usually manifested in the form of the granting of Building Use Rights (HGB) or Use Rights over HPL land, which is based on a land use agreement between the HPL holder as the authority and the investor as the property developer. This study aims to analyze in depth the legal status of HPL following the enactment of regulatory transformation through Law Number 6 of 2023 concerning the Stipulation of the Job Creation Regulation into Law, which was then technically implemented in Government Regulation Number 18 of 2021. This legal reform brought significant changes, particularly in providing certainty over a longer and more integrated period for granting rights. However, on the other hand, this integration also requires strict synchronization between the public interest in protecting state assets and the private interest in obtaining certainty of return on investment. The research findings indicate that while the new regulatory regime offers significant opportunities for optimizing state and regional assets, the existence of HPLs still faces a number of legal and practical challenges. The primary challenge lies in the potential for dual authority in determining the annual mandatory fee rate and the mechanism for recommending rights extensions, which are often considered bureaucratic. This situation creates the risk of cost uncertainty for property investors, given that HPL holders have broad discretionary authority in determining the terms of the cooperation agreements that underlie the issuance of land rights over the HPL. In conclusion, the effectiveness of HPLs as a catalyst for property investment depends heavily on the implementation of transparency and accountability principles by the rights-holding institutions. Strengthening legal certainty for investors must be balanced with a robust oversight mechanism to prevent HPLs from becoming an obstacle to the investment climate due to unprofessional governance. This research recommends standardizing fairer land use agreement clauses and simplifying administrative procedures for rights extensions, in order to create a more competitive and sustainable property investment ecosystem in the future.